Meta-analysis of the intervention effects of tai chi on fasting blood glucose, blood pressure and triglyceride in middle-aged and elderly people - Wenzheng Zhao; Hanyu Ju; Kaituo Zhu (The Aging Male)
Background Hypertension, hyperlipidemia, and hyperglycemia have emerged as global health concerns of paramount significance. With the burgeoning popularity of mind-body therapy, cardiovascular patients have increasingly exhibited a vested interest in the practice of Tai Chi. The objective of this study seeks to quantitatively assess the impact of Tai Chi interventions on blood pressure, lipid levels, and glucose concentrations among the elderly population, thereby explaining the optimal intervention protocol.Methods An extensive search was conducted across multiple databases, including Web of Science, PubMed, CNKI, WANFANG DATA, RISS, KISS, and DBPIA, comprising English, Korean, and Chinese literature. The search strategy employed a retrieval method of subject term 1 + subject term 2, which included both full names and abbreviations of the terms. Specifically, “taijiquan” or “Tai Chi” were set as the Term 1, while Term 2 was set as “blood pressure,” “BP,” “Fasting blood glucose,” “FBG,” “Triglyceride,” and “TG.” Thereafter, the retrieved articles were filtered in accordance with the PICOS method. Risk of bias assessment was performed using RoB 2.0, while data analysis was conducted using Comprehensive Meta-Analysis 3.7.Results A total of 57 studies, including 3,856 research subjects, were eligible for inclusion. The findings of the primary effect quantitative synthesis demonstrated that Tai Chi exerted an improvement on systolic blood pressure (SBP) (ES = −0.764, p < .001), diastolic blood pressure (DBP) (ES = −0.426, p = .001), triglyceride (TG) (ES = −0.452, p < .001), and fasting blood glucose concentrations (FBG) (ES = −0.552, p = .002) among middle-aged and elderly individuals. Subgroup analysis further revealed that the intervention effects were significantly influenced by the characteristics of the research subjects and the specific intervention protocol employed.Conclusion Tai Chi, as a gentle form of aerobic exercise, exerts a profound impact on reducing blood pressure, fasting blood glucose levels, and triglyceride concentrations among middle-aged and elderly individuals. Notably, the intervention effect is particularly pronounced among male patients afflicted with hypertension, hyperglycemia, and hyperlipidemia. Based on the collective advantages underscored by this research, we strongly recommend engaging in Tai Chi exercises for a minimum duration of 16 weeks, with each session lasting 30–50 min and conducted 6–7 times per week, without any restrictions on the style employed.